2018
DOI: 10.3390/chemosensors6010006
|View full text |Cite
|
Sign up to set email alerts
|

Stand-Off Chemical Detection Using Photoacoustic Sensing Techniques—From Single Element to Phase Array

Abstract: Abstract:Technologies that can detect harmful chemicals, such as explosive devices, harmful gas leaks, airborne chemicals or/and biological agents, are heavily invested in by the government to prevent any possible catastrophic consequences. Some key features of such technology are, but not limited to, effective signal-to-noise ratio (SNR) of the detected signal and extended distance between the detector and target. In this work, we describe the development of photoacoustic sensing techniques from simple to mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, the research group demonstrated a signal-enhancement and noise-reduction approach experimentally by means of acoustic beam-former technology with multiple microphone/reflector system, as well as with an array of multiple microphones and one reflector [144,145]. A standoff detection distance of 41 feet in an outdoor setting has been achieved for safely detecting chemicals, such as IPA, RDX, and TNT, with high signal sensitivity [146]. Most recently, Ramesh C. Sharma et al developed a QCL based standoff LPAS with for detection of hazardous molecules contaminants/adsorbed on surfaces, such as plastic and cloth, from short standoff distances [147].…”
Section: Standoff Lpas With Microphonesmentioning
confidence: 99%
“…Subsequently, the research group demonstrated a signal-enhancement and noise-reduction approach experimentally by means of acoustic beam-former technology with multiple microphone/reflector system, as well as with an array of multiple microphones and one reflector [144,145]. A standoff detection distance of 41 feet in an outdoor setting has been achieved for safely detecting chemicals, such as IPA, RDX, and TNT, with high signal sensitivity [146]. Most recently, Ramesh C. Sharma et al developed a QCL based standoff LPAS with for detection of hazardous molecules contaminants/adsorbed on surfaces, such as plastic and cloth, from short standoff distances [147].…”
Section: Standoff Lpas With Microphonesmentioning
confidence: 99%
“…In the past decade, a large number of analytical methods for trace explosive screening have been investigated, including gas chromatography-mass spectrometry (GC-MS) [7][8][9][10], electronic noses [11][12][13][14], ion mobility spectrometry [5,[15][16][17][18], surface acoustic wave devices [19][20][21] and fluorimetry [22][23][24][25]. Some effective approaches, such as solid-phase microextraction (SPME) [26][27][28], have been extensively explored for ultrasensitive gaseous detection of non-volatile explosives at the ppb or ppt level.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, a large number of analytical methods for trace explosive screening have been investigated, including GC-MS [7][8][9][10], electronic noses [11][12][13][14], ion mobility spectrometry [5,[15][16][17][18], surface acoustic wave devices [19][20][21] and fluorimetry [22][23][24][25]. Some effective approaches, such as solid-phase microextraction (SPME) [26][27][28], have been extensively explored for ultrasensitive gaseous detection of non-volatile explosives at ppb or ppt level.…”
Section: Introductionmentioning
confidence: 99%